Improving the Mathematical Problem-Solving Ability of Junior High School Students through Two Stay Two Stray Learning Based on a scientific learning approach on Cube and Block Material - Yusuf, Siti Hajar (Riwayat: Educational Journal of History and Humanities, 2024)
Education is the initial foundation for humans to be able to walk in this life. Since the beginning of human creation, education has become a part of life to be able to adapt to the environment, this pre-experimental research with a one group pretest-posstest research design, the population in this study is all grade VIII students of SMP Negeri 7 Ternate City. The sample of this study was class VIII-i students consisting of 20 students. The data collection of this study used a mathematical problem-solving ability test instrument in the form of an essay. The data were analyzed using descriptive statistics, namely the Benchmark Reference Guidelines (PAP) based on the category of students' mathematical problem-solving ability and normalized N-Gain calculations and inferential statistics using the t-Test for abnormal distribution data. The results showed that: the mathematical problem solving ability of grade VIII-i students of SMP Negeri 7 Ternate City. the application of the Two Stay Two Stray learning model Based on the Scientific Learning Approach can significantly improve students' mathematical problem solving skills on cube and block material.